Transfer of scientific knowledge through training programs for advisors in the field of animal husbandry - Tolimir Nataša; Maslovarić Marijana; Jovanović Rade; Tomić Vedran; Popović Nikola; Stanimirović Ivana; Beskorovajni Radmila (Biotechnology in Animal Husbandry)
The transfer of scientific knowledge and innovation into practice is one of the key factors in improving the productivity and sustainability of animal husbandry. The goal of this paper is to provide a comprehensive overview of training modules on animal husbandry in the period 2015-2024, aimed at strengthening the competencies of agricultural advisors. Having analysed the data on the animal husbandry trainings (56), the authors were given a complete insight into the dynamics, content, quality and effects of these trainings aimed at improving the knowledge and skills of agricultural advisors. The trainings were grouped by thematic area (10), year (10) and knowledge axes - modernization of knowledge (15 trainings) and knowledge expansion (41 trainings). The effects of the trainings and progress in advisors' knowledge were evaluated by using quantitative and qualitative indicators, established from a survey of the trainees. The results of the research indicate a high level of satisfaction of the trainees, considering that the average rating of all trainings was 4.71 (out of 5.00), the progress in knowledge was 44.56% and the applicability of the trainings was rated 4.58 (out of 5.00), which confirms the quality and relevance of the content and the way the trainings were carried out. In the conclusion of the paper, the authors point out the effect of the trainings of advisors in the field of animal husbandry and a need for some future training programs, while respecting the current trends in agriculture.